A chemometric study in the area of feasible solution of an acid–base titration of N-methyl-6-oxyquinolone. Issue 18 (12th March 2018) - Sawall, Mathias; Schmode, Stella; Schröder, Henning; Ludwig, Ralf; Neymeyr, Klaus
Abstract : Multivariate curve resolution methods aim at recovering the underlying chemical components from spectroscopic data on chemical reaction systems. Abstract : Multivariate curve resolution methods aim at recovering the underlying chemical components from spectroscopic data on chemical reaction systems. In most cases the spectra and concentration profiles of the pure components cannot be uniquely determined from the given spectral data. Instead continua of possible factors exist. This fact is known as rotational ambiguity. The sets of all possible pure component factors can be represented in the so-called area of feasible solutions (AFS). This paper presents an AFS study of the pure component reconstruction problem for a series of UV/Vis spectra taken from an acid–base titration of N -methyl-6-oxyquinolone. Additional information on the equilibrium concentration profiles for a varying acid concentration is taken from fluorescence measurements. On this basis chemometric duality arguments lead to the construction of a unique final solution.